VD_FINDINFO Jug / 2021 / 461 vom 16. Februar 2022 - VD Tribunal cantonal (2022)
RISQUE DE CONFUSION, IMITATIONPROPRIÉTÉ INTELLECTUELLE | 2 LCD, 3 al. 1 let. d LCD, 3 al. 1 let. e LCD, 343 al. 1 let. a CPC (CH), 343 al. 1 let. c CPC (CH), 59 al. 2 let. a CPC (CH)